Preparation method and application of porous heterojunction vanadium-based aqueous zinc battery positive electrode
By doping vanadium elements into iron-based MOFs materials, porous heterojunction FeVO oxide positive electrode material is prepared, which solves the problem of efficient reversible insertion/detachment of zinc ions in the prior art, and achieves a water system with high specific capacity and high stability Zinc battery positive electrode material.
Patent Information
- Application Number
- CN202411489614.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-24
AI Technical Summary
In the prior art, due to the decomposition voltage of water, few positive electrode materials can be realized with high efficiency and reversible insertion/detachment of zinc ions, making it difficult to achieve high specific capacity and high stability of the positive electrode materials of aqueous zinc batteries.
The iron-based MOFs material was doped with vanadium elements by template sacrificial method to prepare porous heterojunction FeVO oxide as the positive electrode material, and through its unique structural and component characteristics, electron transport and ion diffusion were improved.
The cathode material has excellent rate performance, cycle stability and high capacity, and can maintain good capacity and stability under high current density. The number of cycles can reach 12,000 times and the capacity retention rate is as high as 95%.
Smart Images

Figure CN119419207A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aqueous zinc battery positive electrode modification, and specifically relates to a preparation method and application of a porous heterojunction vanadium-based aqueous zinc battery positive electrode. Background Art
[0002] In recent years, aqueous zinc batteries (AZIBs) have developed rapidly among all aqueous rechargeable batteries. First, zinc reserves are abundant, accounting for about 0.013% of the earth's crust, and the cost is relatively low; in addition, the metal zinc negative electrode has a low electrode potential (-0.76V vs. SHE) and a sufficiently high specific capacity (820mAh g -1 ) and volumetric capacity (5851 mAh cm -3 ). Secondly, the AA and AAA alkaline dry batteries widely used in daily life are all aqueous batteries based on metal zinc negative electrodes, which shows their own superiority. Since the development of aqueous zinc secondary batteries, the research and development of positive electrode materials has also rapidly expanded from manganese-based materials to vanadium-based compounds, Prussian blue and its derivatives, carbonyl organic compounds and many other types of materials.
[0003] However, due to the limitation of water decomposition voltage, there are relatively few positive electrode materials that can achieve efficient reversible insertion / extraction of zinc ions. Therefore, the development of positive electrode materials for aqueous zinc batteries with both high specific capacity and high stability is still one of the main research directions in the field of aqueous zinc batteries. Summary of the invention
[0004] Technical issues solved:
[0005] The present application aims at the deficiencies in the prior art and solves the technical problems that the current cathode materials that can realize the efficient reversible embedding / ejection of zinc ions are relatively few and are limited by the decomposition voltage of water. The present application provides a method for preparing a porous heterojunction vanadium-based aqueous zinc battery cathode and its application. The FeVO porous heterojunction oxide is prepared by using iron-based MOFs materials as raw materials and adopting a template sacrificial method to dope vanadium elements. The cathode material has a porous heterojunction structure, which can reduce the diffusion barrier, improve electron transport, and enable the electrode to have excellent rate performance, superior cycle stability and high capacity.
[0006] Technical solution:
[0007] To achieve the above objectives, this application is implemented through the following technical solutions:
[0008] A method for preparing a porous heterojunction vanadium-based aqueous zinc battery positive electrode, the steps are as follows:
[0009] Step 1, synthesis of MIL-88A:
[0010] S1. At room temperature, weigh 1.35 g of FeCl3·6H2O and 0.58 g of fumaric acid, dissolve them in 100 mL of deionized water according to mass volume ratio, and mix them evenly to obtain ferric chloride solution and fumaric acid solution;
[0011] S2. Introduce the ferric chloride solution into the fumaric acid solution, stir vigorously for 25-30 minutes, and then transfer the mixed solution to a round-mouth flask and place it in an oil bath at 100°C for 4 hours;
[0012] S3, when cooled to room temperature, the product was collected by centrifuge, and washed with deionized water and ethanol for 3 times respectively; finally, it was dried in a vacuum drying oven at 60°C-80°C for 12 hours to obtain MIL-88A;
[0013] Step 2: Synthesis of FeVO oxide:
[0014] Step a, adding 1.053 g NH4VO3 into 50 mL deionized water according to the mass volume ratio, and vigorously stirring in an oil bath at 70°C-80°C for 1 h to obtain an NH4VO3 solution;
[0015] Step b, uniformly disperse 0.414 g of the pre-prepared MIL-88A in 20 mL of ethanol according to the mass volume ratio, add NH4VO3 solution dropwise, and continue stirring for 1.5-2 h to obtain a reaction mixture;
[0016] Step c, when the reaction mixture is naturally cooled to room temperature, centrifuge with deionized water and ethanol for 3-5 times, and dry the product in a vacuum drying oven at 60°C-80°C for 12 hours;
[0017] Step d, transferring the dried product to a muffle furnace and calcining it at 400° C. for 2 h at a heating rate of 2° C. / min in an air atmosphere to obtain a product recorded as FeVO oxide;
[0018] Step 3: Take active material FeVO oxide by mass percentage: 60%-80%; conductive additive 10%-30%; the rest is binder, the total amount is 100%;
[0019] Step 4: Evenly mix FeVO oxide with conductive additives and adhesives, add 1-2 mL of isopropanol dropwise into the mixture until the surface of the mixture is smooth, and make an electrode film by roller pressing. Finally, press the electrode film onto a mesh current collector to obtain a porous heterojunction vanadium-based aqueous zinc battery positive electrode.
[0020] Furthermore, in the third step, the conductive additive is one or more of Ketjen black KB, activated carbon, mesoporous carbon, graphene, carbon nanotubes, carbon fiber, acetylene black and carbon black; the binder is one of polytetrafluoroethylene PTFE, polyvinylidene fluoride, polyolefin, polyvinyl alcohol and styrene rubber.
[0021] Furthermore, the binder is a polytetrafluoroethylene dispersion with a mass concentration of 40% to 60%.
[0022] Furthermore, in the fourth step, the mesh current collector is a titanium mesh, a nickel mesh or a stainless steel mesh.
[0023] The present application also discloses the use of a porous heterojunction vanadium-based aqueous zinc battery positive electrode prepared by any of the above preparation methods in a fast-charging and discharging aqueous zinc battery or aqueous solution battery.
[0024] Furthermore, the fast charge and discharge aqueous zinc battery uses metallic zinc as the negative electrode material, and the electrolyte is a zinc ion electrolyte.
[0025] Furthermore, the negative electrode material is 0.015 mm thin zinc, 0.035 mm medium zinc or 0.075 mm thick zinc.
[0026] Furthermore, the zinc ion electrolyte is Zn(OTf)2, Zn(ClO) 4、 ZnSO4 or ZnCl2.
[0027] Furthermore, the zinc ion electrolyte has a zinc ion concentration of 0.01 mol / L-10 mol / L.
[0028] Furthermore, the porous heterojunction vanadium-based aqueous zinc battery positive electrode, glass fiber separator and zinc foil electrode were stacked together to form a "sandwich" structure, and a 3M Zn(OTf)2 aqueous solution was used as the electrolyte to prepare a strip Zn / / FeVO2 oxide aqueous battery using a vacuum sealing process.
[0029] Principle explanation: The reason why FeVO oxide materials have excellent performance is that they have unique structural and compositional characteristics as well as good adsorption and diffusion characteristics. From a structural point of view, it has a porous heterogeneous structure. Due to the different work functions and band gaps, a built-in electric field is formed to promote charge separation and transmission. At the same time, its rich pores bring about a mesoporous structure with a high specific surface area, which is conducive to electrolyte penetration and ion diffusion. From a compositional point of view, the multivalent states of iron and vanadium produce multiple pairs of redox reactions during charging and discharging, which increases charge storage and improves capacity, and the interaction between elements stabilizes the structure and improves cycle stability. In terms of adsorption and diffusion, Fe2V4O 13 Surface adsorption of Zn 2+ Strong ability, low adsorption energy and multiple sites enhance the adsorption kinetics. 2+ The diffusion coefficient is high and the ion migration is fast, thereby improving the rate performance and charge and discharge efficiency.
[0030] Beneficial effects:
[0031] The present application provides a method for preparing a porous heterojunction vanadium-based aqueous zinc battery positive electrode and its application, which has the following beneficial effects compared with the prior art:
[0032] 1. This application solves a series of problems that occur in the positive electrode of zinc batteries. The preparation cost is low and can be mass-produced, thereby achieving marketization;
[0033] 2. The application discloses a method for preparing a porous heterojunction vanadium-based aqueous zinc battery positive electrode, which has a porous heterostructure, and the process of forming a built-in electric field to optimize the electronic structure responds quickly and can quickly promote charge transfer;
[0034] 3. The FeVO2 oxide positive electrode of the zinc battery prepared in this application has a current density of 0.6A·g -1 , the cycle can reach 100 times, and the discharge capacity can reach 431mAh·g -1 , showing high capacity characteristics;
[0035] 4. The FeVO2 oxide positive electrode of the zinc battery prepared in this application has a high conductivity at 40A·g -1 Under high current density, it can still maintain good capacity and cycle stability, the number of cycles can reach 12,000 times, and the capacity retention rate is as high as 95%;
[0036] 5. The rate constant current charge and discharge of the FeVO2 oxide positive electrode of the zinc battery prepared in this application is as follows: -1 Gradually increase to 80A·g -1 The charge and discharge curves at 80A·g -1 (11s charging time) still has 250mAh g -1 The high capacity indicates excellent rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a microscopic morphology of the positive electrode of the porous heterojunction vanadium-based aqueous zinc battery of the present application;
[0038] Figure 2 is the XRD powder diffraction pattern of the vanadium-based material of the present application;
[0039] Figure 3 The current density in this application is 0.6A·g -1 Lower cycle performance graph;
[0040] Figure 4 This application is at a current density of 40A·g -1 Lower cycle performance graph;
[0041] Figure 5 This application is at a current density of 0.6A·g -1Gradually increase to 80A·g -1 The constant current charge and discharge curve under the rate. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0043] Example 1
[0044] A method for preparing a porous heterojunction vanadium-based aqueous zinc battery positive electrode, the steps are as follows:
[0045] Step 1, synthesis of MIL-88A:
[0046] S1. At room temperature, weigh 1.35 g of FeCl3·6H2O and 0.58 g of fumaric acid, dissolve them in 100 mL of deionized water according to mass volume ratio, and mix them evenly to obtain ferric chloride solution and fumaric acid solution;
[0047] S2. Introduce the ferric chloride solution into the fumaric acid solution, stir vigorously for 30 min, then transfer the mixed solution to a round-mouth flask and place it in an oil bath at 100°C for 4 h;
[0048] S3, when cooled to room temperature, the product was collected by centrifuge, and washed with deionized water and ethanol three times respectively; finally, it was dried in a vacuum drying oven at 80°C for 12 h to obtain MIL-88A;
[0049] Step 2: Synthesis of FeVO oxide:
[0050] Step a, adding 1.053 g NH4VO3 into 50 mL deionized water according to the mass volume ratio, and vigorously stirring in an oil bath at 70°C-80°C for 1 h to obtain an NH4VO3 solution;
[0051] Step b, uniformly disperse 0.414 g of the pre-prepared MIL-88A in 20 mL of ethanol according to the mass volume ratio, add NH4VO3 solution dropwise, and continue stirring for 2 h;
[0052] Step c, when the reaction mixture is naturally cooled to room temperature, centrifuge with deionized water and ethanol for 3-5 times, and vacuum dry the product at 60° C. for 12 h;
[0053] Step d, transferring the dried product to a muffle furnace, and calcining at 400° C. for 2 h at a heating rate of 2° C. / min in an air atmosphere to obtain a product recorded as FeVO oxide;
[0054] Step 3: by mass percentage: active material FeVO oxide: 60%; conductive additive KB 30%; PTFE 10%;
[0055] Step 4: Evenly mix FeVO oxide with conductive additives and adhesives, add 1-2 mL of isopropanol dropwise into the mixture until the surface of the mixture is smooth, and form an electrode film by rolling. Finally, press the electrode film onto a mesh current collector titanium mesh to obtain a positive electrode.
[0056] The application of porous heterojunction vanadium-based aqueous zinc battery positive electrode in fast charging and discharging aqueous zinc battery uses metal zinc as negative electrode material and the electrolyte is zinc ion electrolyte. The negative electrode shell, two titanium meshes, 0.015mm thin Zn, glass fiber separator, porous heterojunction vanadium-based aqueous zinc battery positive electrode, and positive electrode shell are assembled in order. -1 The Zn(OTf)2 aqueous solution was used as the electrolyte, and the battery was packaged by a battery packaging machine to assemble into a CR2016 button battery, which is denoted as a Zn / / FeVO oxide button battery.
[0057] Example 2
[0058] A method for preparing a porous heterojunction vanadium-based aqueous zinc battery positive electrode, the steps are as follows:
[0059] Step 1, synthesis of MIL-88A:
[0060] S1. At room temperature, weigh 1.35 g of FeCl3·6H2O and 0.58 g of fumaric acid, dissolve them in 100 mL of deionized water according to mass volume ratio, and mix them evenly to obtain ferric chloride solution and fumaric acid solution;
[0061] S2. Introduce the ferric chloride solution into the fumaric acid solution, stir vigorously for 30 min, then transfer the mixed solution to a round-mouth flask and place it in an oil bath at 100°C for 4 h;
[0062] S3, when cooled to room temperature, the product was collected by centrifuge, and washed with deionized water and ethanol three times respectively; finally, it was dried in a vacuum drying oven at 80°C for 12 h to obtain MIL-88A;
[0063] Step 2: Synthesis of FeVO oxide:
[0064] Step a, adding 1.053 g NH4VO3 into 50 mL deionized water according to the mass volume ratio, and vigorously stirring in an oil bath at 70°C-80°C for 1 h to obtain an NH4VO3 solution;
[0065] Step b, uniformly disperse 0.414 g of the pre-prepared MIL-88A in 20 mL of ethanol according to the mass volume ratio, add NH4VO3 solution dropwise, and continue stirring for 2 h;
[0066] Step c, when the reaction mixture is naturally cooled to room temperature, centrifuge with deionized water and ethanol for 3-5 times, and vacuum dry the product at 60° C. for 12 h;
[0067] Step d, transferring the dried product to a muffle furnace, and calcining at 400° C. for 2 h at a heating rate of 2° C. / min in an air atmosphere to obtain a product recorded as FeVO oxide;
[0068] Step 3: by mass percentage: active material FeVO oxide: 60%; conductive additive KB 30%; PTFE 10%;
[0069] Step 4: Evenly mix FeVO oxide with conductive additives and adhesives, add 1-2 mL of isopropanol dropwise into the mixture until the surface of the mixture is smooth, and form an electrode film by roller pressing. Finally, press the electrode film onto the mesh current collector zinc foil to obtain the positive electrode.
[0070] The application of porous heterojunction vanadium-based aqueous zinc battery positive electrode in fast charge and discharge aqueous solution battery, the porous heterojunction vanadium-based aqueous zinc battery positive electrode, glass fiber separator and zinc foil electrode are stacked together to form
[0071] The "sandwich" structure was used, and a 3M Zn(OTf)2 aqueous solution was used as the electrolyte. A strip Zn / / FeVO oxide aqueous solution battery was prepared by a vacuum sealing process.
[0072] Example 3
[0073] A method for preparing a porous heterojunction vanadium-based aqueous zinc battery positive electrode, the steps are as follows:
[0074] Step 1, synthesis of MIL-88A:
[0075] S1. At room temperature, weigh 1.35 g of FeCl3·6H2O and 0.58 g of fumaric acid, dissolve them in 100 mL of deionized water according to mass volume ratio, and mix them evenly to obtain ferric chloride solution and fumaric acid solution;
[0076] S2. Introduce the ferric chloride solution into the fumaric acid solution, stir vigorously for 30 min, then transfer the mixed solution to a round-mouth flask and place it in an oil bath at 100°C for 4 h;
[0077] S3, when cooled to room temperature, the product was collected by centrifuge, and washed with deionized water and ethanol three times respectively; finally, it was dried in a vacuum drying oven at 80°C for 12 h to obtain MIL-88A;
[0078] Step 2: Synthesis of FeVO oxide:
[0079] Step a, adding 1.053 g NH4VO3 into 50 mL deionized water according to the mass volume ratio, and vigorously stirring in an oil bath at 70°C-80°C for 1 h to obtain an NH4VO3 solution;
[0080] Step b, uniformly disperse 0.414 g of the pre-prepared MIL-88A in 20 mL of ethanol according to the mass volume ratio, add NH4VO3 solution dropwise, and continue stirring for 2 h;
[0081] Step c, when the reaction mixture is naturally cooled to room temperature, centrifuge with deionized water and ethanol for 3-5 times, and vacuum dry the product at 60° C. for 12 h;
[0082] Step d, transferring the dried product to a muffle furnace, and calcining at 400° C. for 2 h at a heating rate of 2° C. / min in an air atmosphere to obtain a product recorded as FeVO oxide;
[0083] Step 3: by mass percentage: active material FeVO oxide: 70%; conductive additive acetylene black 20%; PTFE 10%;
[0084] Step 4: Evenly mix FeVO oxide with conductive additives and adhesives, add 1-2 mL of isopropanol dropwise into the mixture until the surface of the mixture is smooth, and form an electrode film by rolling. Finally, press the electrode film onto a mesh current collector titanium mesh to obtain a positive electrode.
[0085] The application of porous heterojunction vanadium-based aqueous zinc battery positive electrode in fast-charging and discharging aqueous zinc batteries uses metal zinc as the negative electrode material and the electrolyte is a zinc ion electrolyte. The negative electrode shell, two titanium meshes, 0.075 mm thick Zn, glass fiber separator, porous heterojunction vanadium-based aqueous zinc battery positive electrode, and positive electrode shell are assembled in order. -1 The Zn(OTf)2 aqueous solution was used as the electrolyte, and the battery was packaged by a battery packaging machine to assemble into a CR2016 button battery, which is denoted as a Zn / / FeVO oxide button battery.
[0086] Example 4
[0087] A method for preparing a porous heterojunction vanadium-based aqueous zinc battery positive electrode, the steps are as follows:
[0088] Step 1, synthesis of MIL-88A:
[0089] S1. At room temperature, weigh 1.35 g of FeCl3·6H2O and 0.58 g of fumaric acid, dissolve them in 100 mL of deionized water according to mass volume ratio, and mix them evenly to obtain ferric chloride solution and fumaric acid solution;
[0090] S2. Introduce the ferric chloride solution into the fumaric acid solution, stir vigorously for 30 min, then transfer the mixed solution to a round-mouth flask and place it in an oil bath at 100°C for 4 h;
[0091] S3, when cooled to room temperature, the product was collected by centrifuge, and washed with deionized water and ethanol three times respectively; finally, it was dried in a vacuum drying oven at 80°C for 12 h to obtain MIL-88A;
[0092] Step 2: Synthesis of FeVO oxide:
[0093] Step a, adding 1.053 g NH4VO3 into 50 mL deionized water according to the mass volume ratio, and vigorously stirring in an oil bath at 70°C-80°C for 1 h to obtain an NH4VO3 solution;
[0094] Step b, uniformly disperse 0.414 g of the pre-prepared MIL-88A in 20 mL of ethanol according to the mass volume ratio, add NH4VO3 solution dropwise, and continue stirring for 2 h;
[0095] Step c, when the reaction mixture is naturally cooled to room temperature, centrifuge with deionized water and ethanol for 3-5 times, and vacuum dry the product at 60° C. for 12 h;
[0096] Step d, transferring the dried product to a muffle furnace, and calcining at 400° C. for 2 h at a heating rate of 2° C. / min in an air atmosphere to obtain a product recorded as FeVO oxide;
[0097] Step 3: by mass percentage: active material FeVO oxide: 70%; conductive additive KB 20%; PTFE 10%;
[0098] Step 4: Evenly mix FeVO oxide with conductive additives and adhesives, add 1-2 mL of isopropanol dropwise into the mixture until the surface of the mixture is smooth, and form an electrode film by rolling. Finally, press the electrode film onto a mesh current collector titanium mesh to obtain a positive electrode.
[0099] The application of porous heterojunction vanadium-based aqueous zinc battery positive electrode in fast-charging and discharging aqueous zinc batteries uses metal zinc as the negative electrode material and the electrolyte is a zinc ion electrolyte. The negative electrode shell, two titanium meshes, 0.075 mm thick Zn, glass fiber separator, porous heterojunction vanadium-based aqueous zinc battery positive electrode, and positive electrode shell are assembled in order. -1 The ZnSO4 aqueous solution is used as the electrolyte, and the battery is packaged by a battery packaging machine to assemble into a CR2016 button battery, which is denoted as a Zn / / FeVO oxide button battery.
[0100] Scanning electron microscope (SEM) test:
[0101] The prepared FeVO was subjected to SEM test to test the morphology of FeVO, such as Figure 1 As shown, it was found that the prepared iron vanadium oxide had a square pyramidal porous structure.
[0102] XRD test:
[0103] The prepared FeVO was subjected to XRD test and compared with Fe2V4O 13 and Fe 0.12 V2O5 standard card comparison, such as Figure 2 , it shows more peaks, indicating the existence of mixed-phase heterogeneous structures in the FeVO oxide samples.
[0104] Cycle performance test:
[0105] like Figure 3 The current density is 0.6A·g -1 The cycling performance of the electrode battery is as high as 431 mAh g -1 The specific capacity is still 428 mAh g after 100 cycles. -1 , the capacity retention rate is as high as 95%.
[0106] Long cycle performance test:
[0107] Figure 4 The current density is 40A·g -1 The cycle performance diagram below shows that the cycle life reaches 12,000 times, the Coulomb efficiency is almost 100%, and the capacity retention rate is as high as 95%.
[0108] GCD test:
[0109] Figure 5 At a current density of 0.6 A g -1 Gradually increase to 80A·g -1 The constant-current charge-discharge curve under high-rate conditions shows that the FeVO oxide cathode exhibits excellent rate capacity at 80 A·g -1 At an ultra-high current density, the battery's charging capacity reaches 252.3 mAh g -1 At the same time, the current density was gradually adjusted to 0.6 A g -1 , the reversible capacity of the battery is fully restored.
[0110] The examples selected in the above materials are for ease of understanding, not to limit the process. People in the same technical field can easily modify the process or transfer it to other cases without creative changes. If these changes also belong to the same claims or similar technologies of the present invention, then the original intention of the invention also includes these changes.
Claims
1. A method for preparing a porous heterojunction vanadium-based aqueous zinc battery positive electrode, characterized in that: Here are the steps: Step 1, synthesis of MIL-88A: S1. At room temperature, weigh 1.35 g of FeCl3·6H2O and 0.58 g of fumaric acid, dissolve them in 100 mL of deionized water according to mass volume ratio, and mix them evenly to obtain ferric chloride solution and fumaric acid solution; S2. Introduce the ferric chloride solution into the fumaric acid solution, stir vigorously for 25-30 minutes, and then transfer the mixed solution to a round-mouth flask and place it in an oil bath at 100°C for 4 hours; S3, when cooled to room temperature, the product was collected by centrifuge, and washed with deionized water and ethanol for 3 times respectively; finally, it was dried in a vacuum drying oven at 60°C-80°C for 12 hours to obtain MIL-88A; Step 2: Synthesis of FeVO oxide: Step a, adding 1.053 g NH4VO3 into 50 mL deionized water according to the mass volume ratio, and vigorously stirring in an oil bath at 70°C-80°C for 1 h to obtain an NH4VO3 solution; Step b, uniformly dispersing 0.414 g of the pre-prepared MIL-88A in 20 mL of ethanol according to the mass-to-volume ratio, adding NH4VO3 solution dropwise, and continuing to stir for 1.5-2 h to obtain a reaction mixture; Step c, when the reaction mixture is naturally cooled to room temperature, centrifuge with deionized water and ethanol for 3-5 times, and dry the product in a vacuum drying oven at 60°C-80°C for 12 hours; Step d, transferring the dried product to a muffle furnace and calcining it at 400° C. for 2 h at a heating rate of 2° C. / min in an air atmosphere to obtain a product recorded as FeVO oxide; Step 3: Take active material FeVO oxide by mass percentage: 60%-80%; conductive additive 10%-30%; the rest is binder, the total amount is 100%; Step 4: Evenly mix FeVO oxide with conductive additives and adhesives, add 1-2 mL of isopropanol dropwise into the mixture until the surface of the mixture is smooth, and make an electrode film by roller pressing. Finally, press the electrode film onto a mesh current collector to obtain a porous heterojunction vanadium-based aqueous zinc battery positive electrode.
2. The method for preparing the porous heterojunction vanadium-based aqueous zinc battery positive electrode according to claim 1, characterized in that: In the third step, the conductive additive is one or more of Ketjen black KB, activated carbon, mesoporous carbon, graphene, carbon nanotubes, carbon fiber, acetylene black and carbon black; the binder is one of polytetrafluoroethylene PTFE, polyvinylidene fluoride, polyolefin, polyvinyl alcohol and styrene rubber.
3. The method for preparing the porous heterojunction vanadium-based aqueous zinc battery positive electrode according to claim 2, characterized in that: The binder is a polytetrafluoroethylene dispersion with a mass concentration of 40% to 60%.
4. The method for preparing the porous heterojunction vanadium-based aqueous zinc battery positive electrode according to claim 1, characterized in that: In the fourth step, the mesh current collector is a titanium mesh, a nickel mesh or a stainless steel mesh.
5. Use of a porous heterojunction vanadium-based aqueous zinc battery positive electrode prepared by any preparation method of claims 1-4 in a fast-charging and discharging aqueous zinc battery or aqueous solution battery.
6. The use according to claim 5, characterized in that: The fast-charging and discharging aqueous zinc battery uses metallic zinc as the negative electrode material and the electrolyte is a zinc ion electrolyte.
7. The use according to claim 6, characterized in that: The negative electrode material is 0.015 mm thin zinc, 0.035 mm medium zinc or 0.075 mm thick zinc.
8. The use according to claim 6, characterized in that: The zinc ion electrolyte is Zn(OTf)2, Zn(ClO) 4、 ZnSO4 or ZnCl2.
9. The use according to claim 8, characterized in that: The zinc ion electrolyte contains zinc ions at a concentration of 0.01 mol / L-10 mol / L.
10. The use according to claim 5, characterized in that: The porous heterojunction vanadium-based aqueous zinc battery positive electrode, glass fiber separator and zinc foil electrode were stacked together to form a "sandwich" structure. A 3M Zn(OTf)2 aqueous solution was used as the electrolyte and a vacuum sealing process was used to prepare a strip Zn / / FeVO oxide aqueous battery.
Citation Information
Patent Citations
MIL-100 (V) derived porous vanadium oxide positive electrode material as well as preparation method and application thereof
CN115448363A
Vanadium-based positive electrode material and preparation method and application thereof
CN115472815A
NiCoFeV-LDH / C composite electrode material with ball-flower-shaped structure and preparation method of NiCoFeV-LDH / C composite electrode material
CN118515322A
Cited By
A Fe-VO material for aqueous zinc ion battery positive electrode and its preparation method and application
CN120545354B